2014
DOI: 10.3906/mat-1306-28
|View full text |Cite
|
Sign up to set email alerts
|

Regular poles for the p-adic group $GSp_4$

Abstract: We compute the regular poles of the L-factors of the admissible and irreducible representations of the group GSp4 , which admit a nonsplit Bessel functional and have a Jacquet module length of at most 2 with respect to the unipotent radical of the Siegel parabolic, over a non-Archimedean local field of odd characteristic. We also compute the L -factors of the generic representations of GSp4 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…5) After determining the asymptotic behavior of φ u we showed that for some choice of u ∈ V Π we have that C , C 1 , and C 2 above are nonzero. In Proposition 5.8 and Proposition 5.11 of [2] it was proved that this is a consequence of the existence of the homomorphisms from the constituents of the Jacquet module to the character Λ, which depends on the Bessel existence conditions. By using these results in Theorem 5.9 of [2] and Theorem 5.16 of [2] we computed the regular poles of each representations that were considered.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…5) After determining the asymptotic behavior of φ u we showed that for some choice of u ∈ V Π we have that C , C 1 , and C 2 above are nonzero. In Proposition 5.8 and Proposition 5.11 of [2] it was proved that this is a consequence of the existence of the homomorphisms from the constituents of the Jacquet module to the character Λ, which depends on the Bessel existence conditions. By using these results in Theorem 5.9 of [2] and Theorem 5.16 of [2] we computed the regular poles of each representations that were considered.…”
mentioning
confidence: 99%
“…3) If the length of the Jacquet module is one, then by Proposition 3.2 of [2], for |x| sufficiently small we have φ u (x) = Cχ(x)…”
mentioning
confidence: 99%
See 3 more Smart Citations